An prospective and observational study of comparison of efficacy and tolerability between metformin and combination of metformin and glibenclamide in the maintence therapy of type 2 diabetes mellitus in a tertiary care hospital (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
BackgroundDiabetes mellitus is one of the most common non-communicable disease world-wide. There are many groups of drugs available for the treatment of type 2 diabetes mellitus. we use these drugs as monotherapy or in combination to maintain normoglycemia. Because of paucity of published reports in the Indian literature regarding the pattern of use, efficacy, safety, tolerability of comparison of therapy of metformin and combination of metformin and glibenclamide, the present study was taken up.ObjectivesTo study the comparison of efficacy, safety and tolerability of metformin and combination of metformin and glibenclamide in achieving normal blood glucose level in type 2 diabetes mellitus.Materials and methods100 properly selected subjects with type 2 diabetes mellitus were included for the present study. The medication were used empirically as monotherapy or fixed dose combination, OD or BID in a continuation manner after the meals. Blood glucose level was measured at the baseline and daily afterwards for one month using standard techniques. The data collected was analyzed statistically using descriptive statistics. Tolerability and patient compliance for the prescribed medications were also assessed during the follow up visits.ResultsCombination therapy reported to control the blood glucose level more efficiently as compared to metformin monotherapy at the end of the study, as 96% of subjects showed normoglycemia as compared to metformin (70%). Also, incidence of hyperglycemic episodes were less in combination therapy.  Subjects with combination therapy reported more side effects compared to metformin alone therapy. The patient compliance for the prescribed medications was excellent.Interpretation and ConclusionBlood glucose level can be effectively maintained under normal limits in Type 2 DM, with combination therapy as compared to monotherapy of metformin.